2016
DOI: 10.1128/jmbe.v17i3.1156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Persistence of Misconceptions in Tree Thinking

Abstract: Darwin described evolution as “descent with modification.” Descent, however, is not an explicit focus of most evolution instruction and often leaves deeply held misconceptions to dominate student understanding of common ancestry and species relatedness. Evolutionary trees are ways of visually depicting descent by illustrating the relationships between species and groups of species. The ability to properly interpret and use evolutionary trees has become known as “tree thinking.” We used a 20-question assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
(24 reference statements)
0
30
0
2
Order By: Relevance
“…As tree-thinking is seen as an increasingly important part of biological literacy (Baum and Smith 2013;Thanukos 2009) it is important to note that students at all educational levels struggle in engaging with evolutionary trees (Catley et al 2012;Gregory 2008;Kummer et al 2016;Omland et al 2008). Different authors have called for the implementation of tree-thinking in school curricula in order to improve students' knowledge of macroevolution (e.g., Baum et al 2005;Catley 2006;Meir et al 2007;Sandvik 2008).…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As tree-thinking is seen as an increasingly important part of biological literacy (Baum and Smith 2013;Thanukos 2009) it is important to note that students at all educational levels struggle in engaging with evolutionary trees (Catley et al 2012;Gregory 2008;Kummer et al 2016;Omland et al 2008). Different authors have called for the implementation of tree-thinking in school curricula in order to improve students' knowledge of macroevolution (e.g., Baum et al 2005;Catley 2006;Meir et al 2007;Sandvik 2008).…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Relying on a single trait or a small number of characteristics is not seen as suitable to get a reliable estimate on the relative relationship of species (Gendron 2000). Different studies have shown that students struggle with understanding evolutionary trees and display a great variety of widespread learners' misconceptions (Baum et al 2005;Gregory 2008;Kummer et al 2016;Meir et al 2007;Omland et al 2008;Thanukos 2009).…”
Section: Tree-thinkingmentioning
confidence: 99%
“…By purposefully overcoming challenges, species become more complex and are therefore "more (highly) developed" than other species. Therefore, the notion of seeing the taxonomic system as an increasing order of complexity could be a consequence of teleological thinking as proposed by Kummer et al (2016). In the course of this work, we will lay out this idea in more detail.…”
Section: Teleology and Evolutionmentioning
confidence: 99%
“…Despite the relevance of tree-thinking, numerous studies show that students struggle with these kinds of representations and that working with evolutionary trees is an issue at all educational levels (Baum et al 2005;Blacquiere and Hoese 2016;Bokor et al 2014;Kummer et al 2016;Meir et al 2007). This can be explained, as numerous known factors can affect the difficulty of reading evolutionary trees.…”
Section: Evolutionary Trees As Representation Of Evolutionmentioning
confidence: 99%
See 1 more Smart Citation